Nuclear Magnetic Resonance Derived Biomarkers for Evaluating Cardiometabolic Risk in Youth and Young Adults Across the Spectrum of Glucose Tolerance - Chung, Stephanie T.; Matta, Samantha T.; Meyers, Abby G.; Cravalho, Celeste K.; Villalobos-Perez, Alfredo; Dawson, Joshua M.; Sharma, Vandhna R.; Sampson, Maureen L.; Otvos, James D.; Magge, Sheela N. (Frontiers in Endocrinology, 2021)
Youth with obesity have an increased risk for cardiometabolic disease but identifying those at highest risk remains a challenge. Four biomarkers that might serve this purpose are “by products” of clinical NMR LipoProfile® lipid testing: LPIR (Lipoprotein Insulin Resistance Index), GlycA (inflammation marker), BCAA (total branched-chain amino acids), and glycine. All are strongly related to insulin resistance and type 2 diabetes (T2DM) in adults (glycine inversely) and are independent of biological and methodological variations in insulin assays. However, their clinical utility in youth is unclear. We compared fasting levels of these biomarkers in 186 youth (42 lean normal glucose tolerant (NGT), 88 obese NGT, 23 with prediabetes (PreDM), and 33 with T2DM. All 4 biomarkers were associated with obesity and glycemia in youth. LPIR and GlycA were highest in youth with PreDM and T2DM, whereas glycine was lowest in youth with T2DM. While all 4 were correlated with HOMA-IR (Homeostatic Model Assessment for Insulin Resistance), LPIR had the strongest correlation (LPIR: r=0.6; GlycA: r=0.4, glycine: r=-0.4, BCAA: r=0.2, all P<0.01). All 4 markers correlated with HbA1c (LPIR, GlycA, BCAA: r≥0.3 and glycine: r=-0.3, all P<0.001). In multi-variable regression models, LPIR, GlycA, and glycine were independently associated with HOMA-IR (Adjusted R2=0.473, P<0.001) and LPIR, glycine, and BCAA were independently associated with HbA1c (Adjusted R2=0.33, P<0.001). An LPIR index of >44 was associated with elevated blood pressure, BMI, and dyslipidemia. Plasma NMR-derived markers were related to adverse markers of cardiometabolic risk in youth. LPIR, either alone or in combination with GlycA, should be explored as a non-insulin dependent predictive tool for development of insulin resistance and diabetes in youth.